The Superinfection of Dermoid Cysts in Nigeria - Onuigbo, Wilson; Nwabunike, Timothy; Ojukwu, Joseph (International Journal of Medical and Health Sciences Research, 2016)
Mature cystic teratoma of the ovary may be complicated by torsion, rupture, and malignant change, but is rarely complicated by infection. Here we report two cases. One was associated with subumbilical hernia operation, and the other followed appendectomy. In all probability, the complication was due to nosocomial infection in this developing community. This is of forensic importance.